Evaluation of Pre-Fixed Biological Tissues Preparation Methods for ATR-FTIR Biospectroscopy: Evaluation of Tissues Preparation Methods for ATR-FTIR - Maryam Ghasemi.K; Farshad H. Shirazi (Iranian Journal of Pharmaceutical Sciences, 2014)
https://doi.org/10.22034/IJPS.2014.15249 Fourier transform infrared (FTIR) spectroscopy in ATR (attenuated total reflection) mode is a powerful tool for studying biomedical samples, which can provide important structural information on the molecular composition.Currently, formalin fixation and paraffin preservation (FFPP) is the preferred source for the histological examination of tissue sections. There is lack of consensus with regard to a standard protocol for de-paraffinization of embedded sections in the field of FTIR spectroscopy for which several approaches have been used. The aim of the present study is to optimize the de-paraffinization procedure for biological samples FTIR spectroscopy. To this aim, Rat’s lung tissue samples were paraffinazed in blocks according to standard procedures. Different exposure, duration, and dewaxing timing protocols using any or combinations of n-hexane, xylene, acetone, and absolute ethanol have been applied on embedded sections. The results were evaluated with the comparison of the spectroscopic outcome from these methods with comparison to fresh tissues dried with other methods, as well as pure paraffin spectra. As a result, although nhexane is an effective dewaxing agent for biological samples after a 24 hours exposure, xylene is a better choice with higher efficiency in less time (6_8 minutes). However, sections that was immersed in xylene for 8 minutes and then rinsed i n acetone for 5 minutes s howed a mide Ӏ a nd П b ands a nd D NA contents i n F TIR spectra better t han o ther strategies. Visualization of the sections has shown that the paraffin is not removed completely. The disappearance of peaks at 1426 & 2850_2950 cm-1 of the FTIR spectrum was used to ensure complete deparaffinization that happened with 15 min xylene embedding, which effects on other cellular structures and subsequently on the spectrums.However it is important to note that these processes are not instantaneous and two important properties of the dewaxing agents are its penetration rate and binding time which obey diffusion law, whereby the depth of penetration was proportional to the square root of time. According to this, we have also demonstrated that using pressure, sample proper thickness and higher surface in ATR spectroscopy play an important role in optimization of spectra & decreasing wave disturbances.